Autonomous vehicle overtaking- an online solution - Usman, G.; Kunwar, F. (2009 IEEE International Conference on Automation and Logistics, 2009)
In the context of intelligent transportation, this paper presents a novel online trajectory-generation method for autonomous overtaking capable of handling emergency situations and aborting the manoeuvre, if required, in a smooth and collision free manner. The proposed methodology is guidance based, real-time applicable, and ensures safety and passenger ride comfort. Based on the principles of rendezvous guidance, the passing vehicle is guided in real-time to match the position and velocity of a shadow target (i.e., rendezvous with) during the overtaking manoeuvre. The shadow target's position and velocity are generated based on real-time sensory information gathered about the slower vehicle ahead of the passing vehicle. The proposed method can be used as a fully autonomous system or simply as a driver-assistance tool. Extensive simulations, some of which are presented herein, clearly demonstrate the tangible efficiency of the proposed method.